1995
DOI: 10.1016/s1078-5884(05)80107-8
|View full text |Cite
|
Sign up to set email alerts
|

A new “closed” in situ vein bypass technique results in a reduced wound complication rate

Abstract: These results indicate that a "closed" technique reduces wound complication rate, without negative effects on the short term patency rates. The "closed" technique results in an increased number of postoperative treatments for residual arteriovenous fistulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…[8][9][10] Although the closed operation itself costs more, the total expenditure for the closed procedure in our study was lower than the open technique due to reduced hospital costs ($6322 versus $8030). 4 More recently, Nelson et al 9 corroborated these findings in their study of 46 endovascular-assisted in situ sa-phenous vein bypass procedures versus a historical control group of conventionally treated patients.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…[8][9][10] Although the closed operation itself costs more, the total expenditure for the closed procedure in our study was lower than the open technique due to reduced hospital costs ($6322 versus $8030). 4 More recently, Nelson et al 9 corroborated these findings in their study of 46 endovascular-assisted in situ sa-phenous vein bypass procedures versus a historical control group of conventionally treated patients.…”
Section: Discussionmentioning
confidence: 83%
“…In our initial evaluation of the entire 97-patient population from this multicenter randomized trial, [4][5][6][7] we found that the closed in situ bypass technique produced fewer wound complications (e.g., infections in 72% of open procedure patients versus 34% in the closed group), mainly due to the use of 2 short incisions, which translated into quicker wound healing and shorter hospitalization. Other investigators have published similar observations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Reifsnyder et al 3 observed a 44% rate of wound complications following ISVB, but overall wound-related morbidity as high as 72% has been reported. 4 Recently, a less invasive method has been devised to minimize the incidence of wound complications accompanying femorodistal reconstructions. Technical advances include a minimally invasive means of performing valvulotomy.…”
mentioning
confidence: 99%